La figura de la emancipación y su incidencia en la materialización del derecho de alimentos para el menor en Guaranda, año 2023. - Maiquiza Toapanta Diego Israel (2025)
The development of this research will be carried out with the objective of establishing the veracity of the hypothesis regarding the research problem, which is the figure of emancipation and its impact on the realization of the right to alimony for minors in Guaranda, year 2023. Judicial emancipation, which grants minors certain attributes of legal capacity, can generate conflicts with the parental obligation to provide alimony, which extends until the age of majority or the child's ability to be self-sufficient. The central point is that, although judicial emancipation seeks to protect minors in vulnerable situations, its application can generate conflicts with the fundamental right to food, recognized in the Constitution (Montecristi, 2008) and regulated in the Code for Children and Adolescents (Nacional, 2003). Through the description of the regulatory framework on judicial emancipation and the right to alimony for minors, we seek to identify the legal effects of emancipation on the exercise of this right and determine the possible violations faced by emancipated adolescents. The objective is to understand how judicial emancipation impacts the guarantee of the right to alimony. The technique applied in this research was a survey with a closed questionnaire of five questions. Likewise, information was collected with the help of a document analysis guide, to establish the theoretical part of the research. Keywords: right to alimony, emancipation, emancipated minor